EDUKASI PELAYANAN GIZI RUMAH SAKIT PADA SISWA SMK NEGERI 1 CERME GRESIK - Supriatiningrum, Dwi Novri; Rahma, Amalia (LPPM Universitas Flores, 2024)
. Vocational High School is secondary education that prepares students for the world of work. One of the majors at SMK is culinary arts. SMK Negeri 1 Cerme, Gresik has a culinary arts department that studies food service. The hospital is one of the places for fieldwork practice for students at SMK Negeri 1 Cerme, Gresik. In particular, students need to understand hospital nutrition services as a good provision for fieldwork practice and then work in hospitals as food service workers. This activity’s purpose was to provide education about food management in hospitals. The method for implementing this service uses socialisation with stages of coordination, material presentation, discussion, monitoring, and evaluation. This activity was attended by 56 grade 12 respondents majoring in culinary arts. 50% of students are 19 years old and 86% are women. In the discussion activity, respondents were asked about the role of food service providers in nutrition services in hospitals and providing special food (diet) for diabetes patients. At the end of the session, which carried out monitoring and evaluation through tests, it was found that 93% of respondents had understood the meaning of food management in hospitals and 89% of them had understood the standard forms of hospital food. It can be concluded that this educational activity needs to be carried out in several activities to increase respondents' understanding. Education activities will be more interesting when there is a performance test on respondents so that the information conveyed can be processed deeply in long-term memory.